0135 Using 'in situ simulation' to identify latent errors in general practice: A pilot study. (2nd November 2015) - Welfare, Emma; Mercer, Simon
Abstract : Background: General practice is under pressure as a front line service and is expected to deal with a wide range of cases. It is inevitable that medical emergencies will occur, although less frequently than in hospital. 1 High risk, low frequency emergencies may lead to difficulty in maintaining expertise and local policies and systems remain untested. In situ simulation is well placed to identify latent errors in order to improve patient safety, team knowledge and confidence. 2 The objective of this pilot study was to assess the role and impact of this within a general practice surgery. Methodology: Using a wireless medium fidelity adult mannequin (HAL® S3201, Gaumard, Florida, US) the following scenarios were undertaken: Anaphylaxis, acute exacerbation of asthma and acute coronary syndrome. Participants including doctors, nurses, health care assistants and receptionists were informed of the learning objectives and scenarios to be undertaken. A video assisted human factors focused debrief occurred immediately after each scenario. A pre and post course questionnaire regarding confidence was completed by participants. Results: Individual confidence in dealing with emergencies was seen to increase most (average 2.52/5.0 to 4.24/5.0 on the Likert scale 3 ). The ability of the practice to effectively deal with emergencies was initially rated as moderate on average (3.53/5.0). This improved to very effective (average 4.80/5.0). Several key latent errors were identified with simple recommendations for improvement made. Potential impact: This pilot study identified key latent errors, which could negatively impact on patient care in the case of an emergency. Participants found the experience educational, with improvements in confidence and knowledge seen. There is a plan to commission this project for further practices within the Merseyside area as part of an ongoing educational programme. References: Bury G, Headon M, Egan M, et al . Cardiac arrest management in general practice in Ireland: a 5-year cross-sectional study. BMJ Open. 2013;3 :e002563. doi:10.1136/bmjopen-2013-002563 Wheeler DS, Geis G, Mack EH, et al . High-reliability emergency response teams in the hospital: improving quality and safety using in situ simulation training. BMJ Qual Saf. 2013;22:507–514 Likert R. A technique for the measurement of attitudes. Arch Psychol.1932;140:1–55